Intorno a un rito di conversione degli Ebrei all’Islām tra Cinquecento e Ottocento - Ioly Zorattini, Pier Cesare (Studi e materiali di storia delle religioni, 2017)
The object of this paper is a peculiar rite I have found in some documents of the Venetian Inquisition of the first half of the 17th century and in the records of European travellers in the Otoman Empire and in the Barbary States of North Africa from the 16th to the 17th century. According to these documents, any Jew who wanted to convert to Islām was required to perform a number of symbolic actions which, in the eyes of the Christians (some at least), looked as if the was required to accept Christianism before converting to Islām. The contents of the rite differ; nevertheless, in all cases the neophite is required to proclaim Jesus as prophet and messiah according to Islamic doctrine. The rationale of this request is in the fact that the Jewish negative position with regard to Jesus was well known. The thorough review of the varying accounts has made it possible to follow the development of the European mentality with regards to Islām in the modern age. The voices of the travellers depict not only their personal culture, believes and knowledge of the Islamic word, but also the changing in the European mentality: in fact the rite drives the attention of the travellers in the 16th and 17th centuries; in the 18th it is hinted at as a curiosity, and in the 19th it is just a shade of memory.